1993
DOI: 10.1159/000147508
|View full text |Cite
|
Sign up to set email alerts
|

Increase in RNA and Glycogen but Not in DNA in Developing Human Macrophages Proven by Integrating Microdensitometry

Abstract: In order to quantitate DNA, RNA and glycogen contents of developing macrophages, blood monocytes were obtained from 19 healthy human subjects and examined after 0, 2, 4 and 6 days of suspension culture. Cytochemical staining was carried out by standard methods using Feulgen, cuprolinic blue and PAS. All specimens from all subjects were stained at the same time. Examination was carried out in an integrating microdensitometer, the staining intensities of individual cells being measured at appropriate wavelengths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Macrophages acquire fat and glycogen stores during development. 24,25 Excessive acquisition of selected fats can also occur, as exemplified by the inflammation of vascular diseases, which involves scavenger macrophages that acquire altered LDL and appear as foamy macrophages accumulating at the sites of atherosclerotic plaques. 26 Some evidence also suggests that fatty acids labelled with 14 C are transferred from macrophages to lymphocytes during lymphocyte stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages acquire fat and glycogen stores during development. 24,25 Excessive acquisition of selected fats can also occur, as exemplified by the inflammation of vascular diseases, which involves scavenger macrophages that acquire altered LDL and appear as foamy macrophages accumulating at the sites of atherosclerotic plaques. 26 Some evidence also suggests that fatty acids labelled with 14 C are transferred from macrophages to lymphocytes during lymphocyte stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that adipocytes and macrophages may be interconvertible 72 and that the number of macrophages present in adipose tissue increases along with fat mass 63 . As adipocytes, macrophages can store fat and glycogen 43, 73, 74 . Lipid storage in macrophages is an important step in the development of another inflammatory disease, atherosclerosis, where plaque lesion progression is correlated with increased number of foam cells, or LDL‐loaded macrophages.…”
Section: Adipose Tissue and Inflammationmentioning
confidence: 99%